Dependency of indexes of the physical development level with the technical preparation structure of qualified water polo players in their playing role. - Poproshaev O.V; Ostrovsky M.V; Chumakov O.V (Kharkov National Pedagogical University, 2012)
Dependency of indexes of the physical development level with the technical preparation structure of qualified water polo players in their playing role. The dependency indexes of the physical development level with the technical preparation structure of qualified water polo players in their various playing roles was considered. It was determined that centre fullback the result of technical preparation depend upon the hands' and its segments' length (hand and arm) and also depend upon the foot's length (shin and foot). Anthropometrical indexes depend on centre forward technical preparation (chest excursion, the trunk length, the body length, the width of shoulders and pelvis). It is associated with the peculiarities of the players' body-build in their playing roles and it is associated with their hydrodynamic indexes. The indexes of technical preparation of middle zone players depend upon the hydrodynamic index of sportsman and his hand power.